The Multiple Faces of Nodular Trichoblastoma: Review of the Literature with Case Presentation - Gerardo Cazzato; Antonietta Cimmino; Anna Colagrande; Francesca Arezzo; Lucia Lospalluti; Sara Sablone; Teresa Lettini; Leonardo Resta; Giuseppe Ingravallo (MDPI AG, 2021)
Trichoblastoma (TB) is a rare biphasic benign adnexal neoplasm originating from follicular germ cells but clinically, it can simulate basal cell carcinoma (BCC), making the diagnosis more difficult. There are several variants of Trichoblastoma and a good knowledge of these is essential for correct diagnosis and management. We report two new cases observed in the last year at our Pathological Anatomy Operative Unit, and conduct a careful review of the literature, from the first description of this lesion by Headington in 1970 to the most recent classifications.